Magic bunny dancing days - Bentley, Sue 1951- (Magic bunny, 2010)
Sara is excited to perform in her dance recital, but when she sprains her ankle in rehearsal, dancing is out. But when Sara meets magical bunny Arrow, her dancing disaster turns into the perfect chance to meet a special friend.